Severe Blunt Liver Injury Complicated by Delayed Massive Hemobilia in a Toddler: A Case Report and Literature Review - Liu, Xiaoming; Sun, Qianqian; Sun, Wenjing; Niu, Qiong; Wang, Zhu; Liu, Chen; Fu, Tingliang; Geng, Lei; Li, Xiaomei (Frontiers in Surgery, 2022)
Introduction: Unintentional injuries remain a leading cause of disability among children. Although most of the pediatric patients suffering blunt liver injury can be successfully treated with nonoperative therapy, the diagnosis and management of delayed life-threatening hemobilia following severe blunt liver injury, especially in the pediatric population, remain a challenge for clinicians. Case Presentation: A previously healthy 2-year-old girl suffered a severe blunt liver injury related to an electric bike, which was inadvertently activated by herself. She initially received nonoperative therapy and had a stable condition in the first two weeks. On the 16th and 22nd postinjury days, the patient presented life-threatening massive hemobila which was confirmed via repeat emergent gastroscopy and hepatic arterial angiography. An emergency selective transarterial embolization of the involved branch of the left hepatic artery was successfully performed. The patient recovered uneventfully and long-term follow-up is needed owing to mild dilatation of the left intrahepatic bile duct. Discussion: Incidental injury in children should be considered as a major public health issue and preventive measures should be taken to reduce its occurrence. Delayed massive hemobilia after severe blunt liver trauma is rare, and its accurate and timely diagnosis via emergency hepatic arterial angiography and selective angioembolization may allow prompt and optimal management to achieve good outcomes in the pediatric population.